Immune‐mediated pathology as a consequence of impaired immune reactions: the IMPATH paradox. Issue 9 (7th August 2022) - Ehl, Stephan; Thimme, Robert
Abstract: Traditionally, immune‐mediated pathology is considered to result from hyperactivity of the immune system. In recent years, however, it has become apparent that, paradoxically, immunopathology can also occur as a consequence of impaired, immune reactions. This insight has important consequences. In the case of hyperactivity, immune suppression is the method of choice for therapy. By contrast, patients suffering from immunopathology as a consequence of impaired immune reactions may benefit instead from immune stimulation or immune reconstitution. This concept is what we call the "IMPATH paradox." The scientific and clinical impact of the IMPATH paradox is the focus of the collaborative research center CRC1160, funded by the German Research Foundation (DFG) since 2015. The CRC examines human and murine model situations, in which the causal link between impaired immune reactions and immunopathology can be explored and better mechanistically defined. In this series of review articles, we wish to place some of these models into the context of the IMPATH paradox and illustrate their potential to stimulate novel perspectives on immunopathology and its therapy. Abstract : The IMPATH paradox: Impaired immune cell activation or effector functions as well as impaired immune cell homeostasis or regulation can be at the basis of a variety of immune‐mediated diseases. This paradox calls for exploring immune stimulation or reconstitution as a therapeutic principle in immunopathology.